Morphology and ecophysiology of Swartzia langsdorffii Raddi. seeds - Vaz, Tatiana Arantes Afonso (2016)
Swartzia langsdorffii Raddi. is a native tree from Atlantic Rain Forest and semi deciduous forest in southeast region of Brazil. This species has large orange fruits, lignified, with abundant resin secretion, high water content and late dehiscence. Each fruit has approximately three large, rounded and brownish seeds, surrounded by a yellow aril, and both of them present high water content after dispersal. According to these characteristics S. langsdorffii seeds could be placed in the recalcitrant group. Although recalcitrant, seeds are dispersed in the dry season, August, the month with the lowest rainfall of the year in Lavras, MG. Thus, the aims of this work were to assess the physiological behaviour of S. langsdorffii seeds regarding its response to desiccation and storage, and evaluate the morphophysiological traits that allow seed viability maintenance after dispersal (Article 1). Additionally, it is aimed to identify the true contribution of S. langsdorffii diaspore to seed survival and germination, and identify mophoanatomical traits that allow these desiccation sensitive seeds to remain viable after dispersal (Article 2). The results found in the Article 1 show that S. langsdorffii seeds are safely classified as recalcitrant. Pores were found distributed in the seed coat and also a great amount of stomata in the hypocotylaxis protoderm. These structures are probably related to gas exchange between seed and surrounding structures. Phenolic compounds were also observed in this area, and according some authors these substances are responsible for seed protection against decomposers and abiotic stresses. Seeds remain viable in the soil for up to seven months without significant reduction in water content, even despite the low rainfall and relative humidity of soil before the beginning of the rainy season. That occurs probably due to pericarp and aril protection. In the Article 2 was possible to verify that seeds do not lose water even when not protected by pericarp and aril, probably due to its shape, size, litter relative humidity and to cutin thickening in the protoderm cell walls. Seeds inside pericarp or surrounded by the aril presented higher water content and germination percentage, evidencing that these structures are not responsible for restriction of water loss but to allow higher seed water content and being the main responsible for S. langsforffii seeds survival and germination after dispersal.